2006
DOI: 10.1042/bc20060054
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of EDEN‐BP is required for specific mRNA deadenylation and binding

Abstract: Background information. mRNA deadenylation [shortening of the poly(A) tail] is often triggered by specific sequence elements present within mRNA 3 untranslated regions and generally causes rapid degradation of the mRNA. In vertebrates, many of these deadenylation elements are called AREs (AU-rich elements). The EDEN (embryo deadenylation element) sequence is a Xenopus class III ARE. EDEN acts by binding a specific factor, EDEN-BP (EDEN-binding protein), which in turn stimulates deadenylation.Results. We show h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…We hypothesize that the cFos ΔB, ΔC and ΔE deletion variants may juxtapose UGUR sites in the RNA substrate and create a more efficient CUG-BP binding region that results in more effective UV cross-linking and faster deadenylation kinetics. This model is consistent with the recent observation by Cosson et al (2006) that oligomerization of the CUG-BP homolog EDEN-BP is required for efficient RNA binding and deadenylation in Xenopus.…”
Section: Resultssupporting
confidence: 81%
“…We hypothesize that the cFos ΔB, ΔC and ΔE deletion variants may juxtapose UGUR sites in the RNA substrate and create a more efficient CUG-BP binding region that results in more effective UV cross-linking and faster deadenylation kinetics. This model is consistent with the recent observation by Cosson et al (2006) that oligomerization of the CUG-BP homolog EDEN-BP is required for efficient RNA binding and deadenylation in Xenopus.…”
Section: Resultssupporting
confidence: 81%
“…Either 50 or 150 pg celf1 mRNA was injected into one-cell-stage zebrafish embryos; as a control, either 50 or 150 pg mRFP mRNA was injected. Because a deletion mutant of the linker domain of human or frog Celf1 (Celf1 linker ) is known to lose its functional activity by losing RNA-binding activity or by preventing oligomerization (Takahashi et al, 2000;Cosson et al, 2006), we used zebrafish celf1 linker as a negative control in this study. To confirm its protein expression in embryos, we injected 50 pg celf1 linker mRNA into one-cell-stage zebrafish embryos, and found that a 26 kDa protein, equivalent to that of mutant protein, was expressed in the manipulated embryos (supplementary material Fig.…”
Section: Mrna and Morpholino Injectionsmentioning
confidence: 99%
“…The Zebrafish protein Brul, a homologue of EDEN-BP with 81% identity, was also shown to preferentially bind to GU-rich RNAs [63]. EDEN-BP and Bru-3 can bind to GRE-RNA as dimers [64], [65] and may require GU-rich sequences of sufficient length to allow dimer formation [66]. In addition to the primary GU-rich sequence, adjacent sequence elements may also be important for assembly of CELF proteins on RNA by allowing optimal secondary structure to facilitate the formation of RNA-protein complexes [67], [68].…”
Section: Biochemistry Of Binding By Celf Proteins To Target Mrnamentioning
confidence: 99%
“…The divergent domain may also facilitate CELF:CELF homotypic interactions [64] which may influence its activity. For example, CELF:CELF interactions appear to activate RNA deadenylation in Xenopus extracts [66].…”
Section: Biochemistry Of Binding By Celf Proteins To Target Mrnamentioning
confidence: 99%